Contemporary Nepali Arts: Blurring the Boundaries among Art Genres - Sharma, Yam Prasad (Curriculum Development Journal, 2020)
Some contemporary Nepali artworks have blurred the boundaries among different art genres like sculpture, painting, music, drama, photography and literature. In a single artwork, we can view the elements of two or more art forms. Three dimensional real objects are put on the two dimensional surface like canvas. Three dimensions are the special characteristics of sculpture whereas there are only two dimensions in painting. Three dimensions in the painting are illusions created by the use of light and shade, and gradation of colors. Artists use photographs and paintings simultaneously in the same work. They take references from photographs and present them in canvas. They also present their paintings, sculptures and photographs along with music, recitation of poems and performance. Some of their canvases present painting and poem side by side in the single space. Both visual art and verbal art coexist in the single canvas. The artists’ creative urge goes beyond all boundaries, codes and established rules of arts. They do not follow the conventional techniques of creating arts. They experiment with forms, techniques, contents and medium. A single artwork has its own way of creation which may not be applicable to other artworks created by the same artist. The artist does not follow these trends but his work may set the new trend for other artists.